Rapid diagnosis of duck Tembusu virus and goose astrovirus with TaqMan-based duplex real-time PCR - Li, Haiqin; Wan, Chunhe; Wang, Zhangzhang; Tan, Jia; Tan, Meifang; Zeng, Yanbing; Huang, Jiangnan; Huang, Yu; Su, Qi; Kang, Zhaofeng; Guo, Xiaoquan (Frontiers in Microbiology, 2023)
The mixed infection of duck Tembusu virus (DTMUV) and goose astrovirus (GoAstV) is an important problem that endangers the goose industry. Although quantitative PCR has been widely used in monitoring these two viruses, there is no reliable method to detect them at the same time. In this study, by analyzing the published genomes of DTMUV and goose astrovirus genotype 2 (GoAstV-2) isolated in China, we found that both viruses have high conservation, showing 96.5 to 99.5% identities within different strains of DTMUV and GoAstV, respectively. Subsequently, PCR primers and TaqMan probes were designed to identify DTMUV and GoAstV-2, and different fluorescent reporters were given to two probes for differential diagnosis. Through the optimization and verification, this study finally developed a duplex TaqMan qPCR method that can simultaneously detect the above two viruses. The lower limits of detection were 100 copies/μL and 10 copies/μL for DTMUV and GoAstV-2 under optimal condition. The assay was also highly specific in detecting one or two viruses in various combinations in specimens, and provide tool for clinical diagnosis of mixed infections of viruses in goose.